Becoming Mr Nice: the Howard Marks archive - Marks, Amber (No Exit Press, 2021)
Welcome to the personal archives of Britain's biggest dope smuggler. For 40 years Howard Marks traversed the globe: an international businessman who became an inmate in America's toughest penitentiary before standing for election in the United Kingdom. Becoming Mr Nice reveals an extraordinary montage of previously unseen material from his roller-coaster life, interwoven with his daughter's incisively researched and deadpan commentary. It includes surveillance footage, intelligence reports, phone transcripts, the business cards and letterheads used as trading fronts, driving licences and passport applications in multiple identities, and cryptic faxes from the Far East. But more than that, it offers a vista onto his many and varied experiences and escapades, through notebooks, personal items and correspondence with the bizarre, wonderful, comic or downright suspicious characters who surrounded him. It includes extracts from a lavishly detailed and hitherto unpublished account of Howard's years on the run (written in confidence for the benefit of his otherwise baffled defence team) together with transcripts from his trial at the Old Bailey, in which he successfully claimed that his involvement in the biggest ever importation of cannabis into the United Kingdom was on behalf of the secret services. Peppered with comic observations from Howard's private letters, this book provides a uniquely personal insight into one of Britain's most remarkable characters